Experience and Challenges of Medium and Small and Medium Enterprises (MSME or UMKM) of Tofu Factories in Increasing Competitiveness - Anita Anung; Sri Indah; As’adi (International Journal of Management and Business, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in Indonesia's economy, especially in the food industry sector such as tofu factories. However, MSMEs face significant challenges in improving their competitiveness, such as fluctuations in raw material prices, limited capital, intense market competition, and lack of access to digital marketing technology. This study aims to analyze the experiences and challenges faced by tofu factory MSMEs and the strategies that can be applied to enhance their competitiveness. The research method used is descriptive qualitative with in-depth interview techniques and direct observations of business owners in Batu City. The research findings indicate that the main challenges include high production costs, limited capital, and lack of product innovation. Strategies that can be implemented include cost efficiency, product diversification, digital marketing utilization, and quality improvement. With the right strategies, tofu factory MSMEs can strengthen their competitiveness and ensure business sustainability in an increasingly competitive market.